PENERAPAN SISTEM AKUNTANSI PADA PERUSAHAAN “KEBAB BOSMAN” - Nurhayati nurhayati; Salma azhar fadhillah; Shafira nuraeni damayanti; Alifa azzahra; Helda putri aryana; O.Feriyanto (Lembaga Pengembangan Kinerja Dosen, 2024)
An accounting information system is a system used to process financial data into information that is useful for management, planning and decision making for both internal and external users in the company. Accounting information systems have an important role for the long-term success of a company. Kebab Bosman is a company that operates in the F&B (Food and Beverage) sector, a type of business that focuses on the food and beverage sector or in Indonesian it is also called culinary business or business. The purpose of this research is to find out how the accounting system is used at Kebab Bosman. The method used in this research is qualitative, a method that focuses on in-depth observation. The object of this research is Kebab Bosman and the subjects of the research are the parts involved in the accounting system. Data collection techniques use observation and interviews. Based on the research results, it can be concluded that the implementation of the accounting system at Kebab Bosman has not completely gone well. This can be seen from the dual role (dual work) experienced by one of the employees.